1 - Le Système de Santé au Maroc entre les Contraintes Financières et les Exigences Sociales: by Ahmed El Hariti - Ahmed El Hariti (Africa Development, 1988)
The analysis of the health sector provides an understanding of the specificity of the social function of the state in the reproduction of the labour force as well as its ideological function in the legitimation of the estab lished order. The contemporaiy crisis and the austerity measures imposed by the international financial institutions have deleterious impact on the health sector. In Morocco, the financial resources allocated to the public health sector are declining in real value and as a proportion of the overall budget of the state. Consequently, one witnesses a sharpening of the social and regional ine qualities in the health delivery system. These budgetary cuts are introduced at a time of rapid population growth, accelerated urbanization, the introduction of new values and norms of consumption and production as well as a progressive awareness by the population of their rights to health. All these factors have'in-. creased and broadened the health needs and require the augmentation of resources allocated to the health sector. Caught under this double pressure of financial constraint and social exigency, the state ought to look for alternative possibilities of augmenting resources for the health sector.